2009
DOI: 10.3945/jn.108.098277
|View full text |Cite
|
Sign up to set email alerts
|

National Estimates of Dietary Fructose Intake Increased from 1977 to 2004 in the United States

Abstract: Our purpose was to conduct a new analysis to update and extend previously published trends of fructose availability and estimated fructose intake and food sources of dietary fructose from the 1977-1978 Nationwide Food Consumption Survey (NFCS) data. We estimated fructose usual intake with data from NHANES 1999-2004 for 25,165 individuals (1 y and older, excluding pregnant and lactating women and breast-fed infants) using the Iowa State C-SIDE software. We applied food group-specific conversion factors to indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
360
3
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(382 citation statements)
references
References 35 publications
3
360
3
15
Order By: Relevance
“…Several surveys, using various epidemiologic methods to assess dietary intakes, have consistently reported that total sugar consumption, added sugar intake, and fructose have indeed increased worldwide over the past three decades [56], reviewed in [6]. In the US, average fructose consumption has increased from about 37 g/d in the late 1970s [56] to 49 g/d in the 1999-2004 period [57]. Not only fructose, but also total energy intake, increased during the same period.…”
Section: Do Changes In Fructose Consumption Explain the Current Epidementioning
confidence: 99%
“…Several surveys, using various epidemiologic methods to assess dietary intakes, have consistently reported that total sugar consumption, added sugar intake, and fructose have indeed increased worldwide over the past three decades [56], reviewed in [6]. In the US, average fructose consumption has increased from about 37 g/d in the late 1970s [56] to 49 g/d in the 1999-2004 period [57]. Not only fructose, but also total energy intake, increased during the same period.…”
Section: Do Changes In Fructose Consumption Explain the Current Epidementioning
confidence: 99%
“…W latach 1977-1978 spożycie fruktozy wynosiło 37 g/d, podczas gdy w okresie 1999-2004 wzrosło o 32-49g/d. Wzrost konsumpcji fruktozy w dużej mierze związany był ze wzrostem spożycia produktów, do których dodawana jest ona w procesach technologicznych, głównie pod postacią syropu glukozowo-fruktozowego [5].…”
Section: Spożycie Fruktozyunclassified
“…Auch das Disaccharid Saccharose, der gewöhnliche Haushaltszucker, enthält Fruktose, denn es besteht jeweils aus der Verbindung eines Fruktosemoleküls mit einem Glukosemolekül (20). Fruktose und Fruktose-haltige Sirupe werden in der Lebensmittelindustrie vielfältig und umfangreich eingesetzt (36,(43)(44)(45)57) (Anhang Tab. 18), (Abb.…”
Section: Abbunclassified
“…Jahrzehnte insbesondere in Ländern wie beispielsweise den USA zu (44,45): Lag in den USA der 70ger Jahre der durchschnittliche Verzehr an Fruchtzucker noch bei 37g/Tag/Person (45,58), so werden heutzutage durchschnittlich 49g/Tag/Person (45) Fruktose und bei jungen Männern sogar durchschnittlich 75g/Tag/Person (45) konsumiert.…”
Section: Der Einsatz Und Verzehr Von Fruktose Nahmen Insgesamt Innerhunclassified